ANALISIS PENGATURAN KRITERIA FASILITAS PENANAMAN MODAL DIKAITKAN DENGAN PRINSIP MOST FAVORED NATION (MFN) - Wulan Kesuma Wardani, Ni Made; Sarna, Kadek (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014)
Capital investment is one of the government's measures to improve the national economy. Article 18 of the Investment Law Number 25 of 2007 regulating investment facilities provided to investors is the government's efforts in order to attract investors to invest in Indonesia. In addition, to avoid the negative effect of the investor who will dominate the fields of activity are the same or are public because some of the criteria set forth in the provisions of Article 18 paragraph (3) of the Act. In writing scholarly journals used this type of research is normative research. Investment facilitation with this criterion slightly deviate from the principle of Most Favored Nation (MFN), which requires the government to provide equal treatment to all state investors. This will affect the existence of discrimination by Indonesian objections, causing the investment to invest in Indonesia.
Keywords: Facilities , Investment, Criteria , Most Favored Nation (MFN)